SOLIDARITAS DALAM PERSPEKTIF HADITS TEMATIK - Muhammad Gufron; Muhammad Alif (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
This study examines the concept of solidarity from the perspective of the Prophet Muhammad’s ﷺ hadiths using a thematic (maudhū‘ī) hadith approach. The research is motivated by the decline of social solidarity in modern society due to increasing individualism and pragmatic social relations. Employing a qualitative library-based method, the study draws upon authentic hadith sources such as Ṣaḥīḥ al-Bukhārī, Ṣaḥīḥ Muslim, Sunan Abī Dāwūd, and Sunan al-Tirmidhī, supported by relevant academic literature. The analysis involves thematic inventory, classification, and interpretation of hadith texts. The findings reveal that solidarity in hadith encompasses spiritual, social, moral, and humanitarian dimensions rooted in faith, brotherhood (ukhuwah), mutual assistance (ta‘āwun), compassion, justice, and collective responsibility. Solidarity is thus understood not merely as a social ethic but as a manifestation of faith that strengthens social cohesion and enhances spiritual well-being, making it highly relevant as a framework for social ethics in contemporary society.